The Effect of an Integrated Islamic Curriculum in English Classes - Fayza Nur Amalia; Esliana; Kalayo Hasibuan (Edu-Ling: Journal of English Education and Linguistics, 2025)
The impact of incorporating Islamic beliefs into English language training on students' language skills, character development, and cultural awareness is examined in this study. A comprehensive educational experience is produced by the curriculum's integration of ethical and culturally relevant material, such as Islamic history and moral quandaries, into English classes. This method fosters intercultural competency while improving vocabulary acquisition, critical thinking, and ethical reasoning, as evidenced by thematic analysis of case studies and existing literature. However, issues like inadequate teacher preparation and a lack of standardized resources underscore the necessity of institutional assistance. The study highlights the transformative potential of faith-based curricula in bringing language acquisition into line with cultural and moral goals, offering guidance to educators and policymakers on how to create inclusive and productive learning environments.